IS LEGALESE A GOOD MEDIUM OF COMMUNICATION? - AN EMPIRICAL STUDY - Yadav, Suman; Shivali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India became independent 77 years ago. It marked a new beginning for the country. It became more nationalised in its approach. India started supporting local businesses and moving towards self-sufficiency. We gave ourselves a new constitution which mapped the development of our beloved multi-linguistic, multi-cultured nation. We started re-writing our laws adept to our needs. The language of the laws however, still remains the same. It won’t be wrong to say that each profession has its own language, certain terms that are privy to that particular group of people. The legal field also has a different language, also commonly known as the “legalese”. It is predominantly archaic English consisting of Latin and French terms. As a layman we deal with multiple transactions daily and end up following and breaking many a laws, intentionally or unintentionally, but mostly unintentionally. In the famous case of State of Maharashtra versus MH George, the court recognized an important principle of the nation- Even a stranger passing through the nation must be aware of the laws of our nation. It puts an added responsibility for Indian citizens to be aware of the laws of the nation. Some jurists claim the use of legalese is used in the drafting of laws because of the precision it provides. This article shows empirically how difficult it is to comprehend legalese and how it can be simplified while preserving precision to be made more accessible using plain language. One of the aims of the Indian Knowledge System is to make knowledge accessible. Language plays a pivotal role in education. Once the legal language is simplified it becomes easier not only to comprehend but also to translate it into multiple other regional languages of India. The article also shows how the simplified version of the law can be easily translated into a more comprehensive translation into “Hindi” language of the same provision.